How to enhance your mathematics subject knowledge : number & algebra for secondary teachers - Sherwood, Jemma (Oxford, United Kingdom : Oxford University Press, 2018)
This book explores a broad range of the trickiest concepts and misconceptions in the number and algebra topics of secondary maths. From supporting the mastery approach, to answering those awkward but brilliant questions in class, it is crucial reading for all secondary maths teachers wishing to enhance or refresh their own subject knowledge.
Includes index.
JHS
Text in English
Keywords: Mathematics -- Study and teaching (Secondary) -- Great Britain; Mathematics teachers -- Training of -- Great Britain